(untitled) (Current Horticulture, 2024)
Anatomical and molecular analysis of genetic variability was investigated by using SDS-PAGE and RAPD markers in 6 epiphytic orchids, i.e. four species of Bulbophyllum and two of Dendrobium, collected from Southern Ghats of Sikkim, India. The Bulbophyllum careyanum (W.J. Hook.) Spreng., B. maculosum Schltr., B. thomsonii J. D. Hook., B. tremulum Wight., Dendrobium anceps Sw. and D. crassinode Benson and Rchb. f. were collected from East and West Sikkim. A low stomatal frequency and an extensive lignification on inner walls, and handle-cells were recorded in populations collected from East Sikkim (Pakyong) as compared to those from Central-Sikkim (Gangtok). The RAPD and protein profile data indicated intra-population diversity between these two sites which may be attributed to ecological and climatic conditions prevailing in both sites of North-East Himalayas.